From dissection of fibrotic pathways to assessment of drug interactions to reduce cardiac fibrosis and heart failure - Gloria Garoffolo; Maurizio Pesce (Elsevier, 2021)
Cardiac fibrosis is characterized by extracellular matrix deposition in the cardiac interstitium, and this contributes to cardiac contractile dysfunction and progression of heart failure. The main players involved in this process are the cardiac fibroblasts, which, in the presence of pro-inflammatory/pro-fibrotic stimuli, undergo a complete transformation acquiring a more proliferative, a pro-inflammatory and a secretory phenotype. This review discusses the cellular effectors and molecular pathways implicated in the pathogenesis of cardiac fibrosis and suggests potential strategies to monitor the effects of specific drugs designed to slow down the progression of this disease by specifically targeting the fibroblasts.